Ge/Si heterojunction photodetector for 1.064 μm laser pulses - Ismail, Raid A.; Koshapa, Jospen; Abdulrazaq, Omar A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2006)
Iso- and anisotype heterojunction Ge/Si photodetectors were made by depositing Ge layer onto monocrystalline Si using a vacuum evaporation technique. These detectors before and after annealing were utilized to detect 1.064 µm Nd:YAG laser pulses. The study also included determination of the optimal Ge thickness and annealing conditions. The experimental results show that the photoresponse was highly improved after classical thermal annealing and rapid thermal annealing (RTA). The voltage responsivity and signal rise time results strongly depended on the annealing type and conditions. It was found that the optimal conditions can be obtained for n-Ge/p-Si photodetector prepared with Ge 200 nm thick and treated with RTA at 500 ºC for 25 s.